Modified direct torque control method for induction motor drives based on amplitude and angle control of stator flux - Yuttana Kumsuwan (2018)
This paper proposes design and implementation of a direct torque controlled induction motor drive system. The method is based on control of separation between amplitude and angle of reference stator flux for determining reference stator voltage vector in generating PWM output voltage for induction motors. The objective is to reduce electromagnetic torque ripple and stator flux droop which result in a decrease in current distortion in steady-state condition. In addition, the proposed technique provides simplicity of a control system. The direct torque control is based on the relationship between instantaneous slip angular frequency and rotor angular frequency in adjustment of the reference stator flux angle. The amplitude of the reference stator flux is always kept constant at rated value. The system has been implemented to verify its capability such as torque and stator flux responses, stator phase current distortion both during dynamic and steady state with load variation, and low speed operation. © 2008 Elsevier B.V. All rights reserved.